Hemostatic effect of nasal saline irrigation during endoscopic sinus surgery : a systematic review and meta-analysis - Nagarajah, Darshini (2020)
Introduction: Intraoperative hemostasis is crucial for adequate anatomical visualization during endoscopic sinus surgery (ESS) and has been identified as gold-standard treatment for medically refractory chronic rhinosinusitis (CRS). Effective surgery is termed upon adequate identification of anatomic structures, good surgical visualization and controlled bleeding throughout the surgery. Nasal saline irrigation is a novel technique to reduced intra-operative bleeding during endoscopic sinus surgery. Objective: The aim of this research is to assess the suitable and optimum temperature for nasal saline irrigation during endoscopic sinus surgery with regards to bleeding control and quality of surgery site during endoscopic sinus surgery(ESS). Methods: Three authors independently conducted an electronic search via (PubMed, SCOPUS, Google Scholar) and (Cochrane) from their origination to September 2018. The included studies compared nasal saline irrigation (hot saline /warm saline irrigation (HSI/WSI) versus room temperature/normal saline irrigation (RTSI/NSI) during ESS. The outcomes of interest were bleeding score(BS), mean arterial pressure(MAP), duration of the surgery(DS), blood loss (BL), and the surgeon satisfaction score (SS). Results: Based on three studies with a total of 212 patients providing the data, we found that WSI/ HSI produced a better outcome compared to the RTSI/NSI group in the surgical field quality (Mean Difference (MD)= -0.51, 95% CI [-0.84,-0.18], P<.003, I2=72%), 3 studies consisting 237 patients ;moderate certainty. There was no significant difference between the two comparison group in regard to mean arterial pressure ( Mean Difference(MD)= -0.60, 95% CI [-2.17, 0.97], P=0.45, I2=0% , 3 studies with 237 patients; moderate certainty. The surgeons’ satisfaction about the significant reduction in bleeding during the operation showed that there was significant decrease in bleeding in WSI/HSI compared to RTSI/NSI in two studies (Risk ratio = 0.18, 95% CI [ 0.09, 0.33] P<0.001, I2= 0% , 2 studies with 175 patients ; moderate certainty). The volume of blood loss was also significantly higher in groups under RTSI/NSI than HSI/WSI in all the studies reviewed (Mean Difference (MD)=56.4, 95% CI[-57.30, -55.51], P<0.001,I2=0%; moderate certainty). The duration of surgery showed significant increase in RTSI/NSI group than HSI/WSI group in all the studies (Mean Difference (MD)= -9.02, 95% CI [-11.76, -6,28], P<0.001, I2=0% , 3 studies with 237 patients ; moderate certainty). Conclusion: The evidence from this review suggests that WSI/HSI group are statistically better compared to RTSI/NSI group. Also, no beneficial or detrimental effect of surgeons’ satisfaction score could be determined based on existing evidence. However, since very small number of studies were recruited, further trials are needed to establish the results of this study.